Reflecting on the Self: Introspective Construction of the Feminine in Nineteenth-Century Poets Carolina Valencia and Carolina Coronado - Johnson, Rhi (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2021)
This essay explores the construction of the female creative self in nineteenth-century Spain and introduces the virtually unstudied poet Carolina Valencia (born 1860 in Valladolid) through her poem “A la margen del arroyo” (1890). It brings Valencia into dialogue with the established canon through a parallel reading of the construction of subjectivity in Carolina Coronado’s “El jilguero y la flor del agua” (1852). This reading of subjectivity interacts with various aspects of nineteenth-century Spanish femininity: the identification with nature, the dichotomy of the angel and the monster, and the language of sentimentality.